Influence of Different Organic Waste Materials on the Transformation of Nitrogen in Soils - Das, D.K. (ScientificWorldJournal, 2001)
Organic waste materials like crop residues, well-decomposed cow dung, composts, and other rural and urban wastes are considered highly useful resources in enhancing soil fertility and also in build-up of soil organic matter. Organic matter decomposition provides plant nutrients in soil, which in turn increases crop productivity. Availability of nutrients and nitrogen (N) and phosphorus from organic waste materials is dependent upon the nature of organic residues, climatic conditions, and soil moisture activity. Keeping these factors in view, the present investigation was undertaken to study the transformation of N from different organic waste materials in two contrasting soils from an eastern India, subtropical region. The results showed that the amounts of ammoniacal-N (NH(4)-N), nitrate-N (NO(3)-N), hydrolysable N (HL-N), and nonhydrolysable (NHL-N) were increased for up to 60 days of soil submergence and increased further with the increase (1% by weight of soil) of organic residue application. Considering the effect of various organic waste materials, it was found that the amounts of NH(4)-N, NO(3)-N, HL-N, and NHL-N were higher with the application of groundnut hull as compared to wheat straw and potato skin, which may be due to relatively narrow carbon:N ratio of groundnut (22:43) than that of wheat straw (62:84) and potato skin (71:32); however, the results showed that the release of NH(4)-N, NO(3)-N, HL-N, and NHL-N was in the order of groundnut hull > wheat straw > potato skin.